High-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure as well as preparation method and application of high-performance photocatalytic synergistic adsorption material

By introducing the ZIF-67 nano structure and reducing oxygen oxygenhene compound hydroxyl tin zinc acid structure in the photocatalytic material to form a stable porous three-dimensional network structure, it solves the problem of insufficient adsorption and stability of existing photocatalytic materials. Efficient heavy metal adsorption and organic matter degradation are suitable for sewage treatment and soil repair.

CN119368144AActive Publication Date: 2025-01-28SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411506030.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing photocatalytic materials have problems such as few surfactant sites, insufficient adsorption capacity, poor stability and high cost in the fields of environmental governance and energy conversion. The stability of traditional MOFs in aqueous solutions is poor, which limits their in water treatment. Application.

Method used

Adopt a high-performance photocatalytic collaborative adsorbing material containing ZIF-67 nanometer structure. It is loaded to the adsorption gel through the water thermal synthesis method and in-situ growth technology through the water thermal synthesis method and original growth technology, and through the Siter, through Sifif Alkali modification and cross -linking form a stable porous three -dimensional network structure.

Benefits of technology

Achieve high stability, photocatalytic activity and excellent adsorption performance, for sewage treatment or soil repair, high -efficiency adsorption of heavy metals and degradable organic pollutants, and the preparation method is simple, the cost is low, and it can be used in a wide range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368144A_ABST
    Figure CN119368144A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nano-structure and a preparation method and application thereof.According to the adsorption material, aminated natural polysaccharide serves as a raw material, a reduced graphene oxide composite zinc hydroxystannate structure is loaded on adsorption gel through an in-situ growth technology and a hydrothermal synthesis method, and the high-performance photocatalytic synergistic adsorption material containing the ZIF-67 nano-structure is obtained. The mechanical strength and the water stability of the composite material are improved; meanwhile, a metal organic framework ZIF-67 porous material is adopted, so that the adsorption selectivity and affinity of the material to specific metal ions are further improved; in addition, by introducing montmorillonite and potassium humate, the conjugation and chelation coordination between active binding sites of the three-dimensional network structure and pollutants are further enhanced, the efficiency of the adsorption material is improved, and a foundation is laid for wide application of the adsorption material in the field of photocatalytic synergistic adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to a photocatalytic synergistic adsorption material, and specifically relates to a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, and a preparation method and application thereof. Background Art

[0002] With the acceleration of industrialization and the continuous growth of population, environmental pollution is becoming increasingly serious, especially water pollution and soil pollution have become global environmental problems. Heavy metal ions such as lead, mercury, cadmium, etc. pose a huge threat to the environment and human health due to their high toxicity, strong bioaccumulation and difficulty in degradation. Therefore, the development of efficient, economical and environmentally friendly heavy metal ion adsorption materials has become a research hotspot.

[0003] rGO / ZnSn(OH) 6 The composite material is a photocatalytic material with excellent performance, combining the excellent electron mobility and specific surface area of ​​reduced graphene oxide (rGO) and zinc hydroxystannate (ZnSn(OH) 6 ) has a photocatalytic performance, and the composite material maintains the photocatalytic performance of ZnSn(OH) 6 The typical perovskite crystal structure of face-centered cubic stacking is beneficial to improve the stability and photocatalytic activity of the material. Traditional photocatalysts have shown great potential in the fields of environmental governance and energy conversion, but they also have some shortcomings, such as few surface active sites, insufficient adsorption capacity, poor stability and high cost.

[0004] Metal-organic frameworks (MOFs) are a class of porous materials composed of metal ions and organic ligands connected by coordination bonds. They are widely used in wastewater treatment due to their high specific surface area, adjustable pore size and functionalized surface. However, traditional MOFs have poor stability in aqueous solutions, which limits their application in water treatment.

[0005] In summary, a novel rGO / ZnSn(OH) 6 The new nanostructured adsorption material with the advantages of ZIF-67 is of great significance for improving water treatment efficiency, enhancing material stability, photocatalytic activity and solving environmental pollution problems. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure and its preparation method and application, which has high stability, photocatalytic activity and excellent adsorption performance, and is used for sewage treatment or soil remediation to achieve efficient heavy metal adsorption and organic matter degradation. The preparation method is simple, the cost is low, and it can be used on a large scale.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, comprising the following steps:

[0009] Step 1: Weigh 10-20 parts of zinc acetate and 10-20 parts of tin tetrachloride by mass, dissolve them in 80-100 parts of water, and perform hydrothermal reaction at 85-95°C for 8-10 hours. Separate the solid product, wash and dry it to obtain ZnSn(OH) 6 , further ZnSn(OH) 6 dispersed in 20 to 30 parts of a hydrochloric acid solution having a pH of 4 to obtain a suspension A;

[0010] According to the mass fraction, 0.5-0.8 parts of GO were weighed and dispersed in 20-30 parts of water to obtain suspension B;

[0011] The suspension B was slowly added dropwise to the suspension A, and after irradiation with ultraviolet light for 0.5 to 1 h, ultrasonic treatment was performed for 0.5 to 1 h, stirring was performed for 2 to 3 h, and the suspension was allowed to stand for 3 to 5 h. The solid product was separated, washed, and dried to finally obtain rGO / ZnSn(OH) 6 Composite materials;

[0012] Step 2: According to the mass fraction, 3 to 5 parts of rGO / ZnSn(OH) 6 and 1 to 3 parts of natural polysaccharide are dissolved in 80 to 100 parts of 2% glacial acetic acid by mass, stirred until uniformly mixed, then 1 to 2 parts of montmorillonite and 1 to 3 parts of potassium humate are added, and at the same time, 0.5 to 0.8 parts of porogen and 0.3 to 0.5 parts of surfactant are added, and after stirring at a temperature of 40 to 50° C. for 1 to 2 hours, 1 to 2 parts of crosslinking agent are added to form a preliminary adsorption gel containing a Schiff base structure through crosslinking;

[0013] Step three, mix 2-methylimidazole, cobalt nitrate hexahydrate, methanol and water in a mass ratio of (0.6-0.8): (0.4-0.6): (30-40): (20-30), stir until the solution is clear and uniform to obtain a mixed solution, add the preliminary adsorption gel prepared in step 2 to the mixed solution in a mass ratio of (50-75): (85-110), stir for 1-2 hours, and freeze-dry to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructures.

[0014] The present invention also has the following technical features:

[0015] Preferably, the natural polysaccharide includes any one of carboxymethyl chitosan, chitosan oligosaccharide, hyaluronic acid and gelatin.

[0016] Preferably, the porogen includes any one of sodium carbonate, sodium bicarbonate, polymethacrylate, and polyvinyl alcohol.

[0017] Preferably, the surfactant includes any one of sodium dodecylbenzene sulfonate, sodium stearate and sodium oleate.

[0018] Preferably, the cross-linking agent includes any one of glutaraldehyde, eicosanedial, acrolein, and succinaldehyde.

[0019] Preferably, the stirring rate in step 2 and step 3 is 300-500 r / min.

[0020] The present invention also protects a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure prepared by the method as described above and its application in water treatment or soil remediation.

[0021] Compared with the prior art, the present invention has the following technical effects:

[0022] The present invention uses amino natural polysaccharides as raw materials to prepare primary gels, and through in-situ growth technology and hydrothermal synthesis, reduces graphene oxide composite hydroxy zinc stannate structure is loaded on the adsorption gel, so as to improve the mechanical strength and water stability of the composite material, and can not only enhance the adsorption capacity of organic pollutants through π-π interaction, but also photocatalytic degradation and adsorption of benzene and its homologues through photocatalytic synergistic adsorption, so as to realize the concept of green and environmentally friendly treatment of pollutants; by adding montmorillonite and potassium humate, the exchange, adsorption and chelation with metal ions are further enhanced; by using a metal organic framework ZIF-67 porous material with good hydrothermal stability and rich pore structure, by performing Schiff base modification on ZIF-67, Schiff base modification can introduce more active sites, which can promote the pollutant molecules. The adsorption and conversion of the metal ions are increased to increase the adsorption selectivity and affinity for specific metal ions; montmorillonite and potassium humate are introduced to combine with the adsorption gel loaded with the reduced graphene oxide composite hydroxystannate zinc structure, and further cross-linked with the metal organic framework ZIF-67 porous material to form a stable porous three-dimensional network structure. At the same time, the conjugation and chelation coordination between the active binding sites of the three-dimensional network structure and the pollutants improve the efficiency of the adsorption material; by adding surfactants and porogens, the pores and pore density of the porous material can be increased to further improve its adsorption capacity, and finally a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure with high stability, photocatalytic activity and excellent adsorption performance is prepared, which can be used for sewage treatment or soil remediation to achieve efficient adsorption of heavy metals and degradation of organic pollutants;

[0023] The preparation method of the invention is simple, low in cost and can be used on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a diagram of the preparation mechanism of Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0026] Example 1

[0027] This embodiment provides a method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, comprising the following steps. The reaction mechanism is as follows: Figure 1 As shown:

[0028] Step 1: According to the mass fraction, 10 parts of zinc acetate and 20 parts of tin tetrachloride were weighed, dissolved in 95 parts of water, and hydrothermally reacted at 85°C for 10 hours. The solid product was separated, washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to obtain ZnSn(OH) 6 , further dispersed it in 25 parts of hydrochloric acid solution with a pH of 4 to obtain suspension A; weighed 0.7 parts of GO and dispersed it in 30 parts of water to obtain suspension B; slowly added suspension B to suspension A, and after irradiating it with ultraviolet light for 1 hour, ultrasonicated it for 0.5 hours, stirred it for 3 hours, and allowed to stand for 3 hours. The solid product was separated and washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to finally obtain rGO / ZnSn(OH) 6 Composite materials;

[0029] Step 2: According to the mass fraction, 4 parts of rGO / ZnSn(OH) 6 and 3 parts of carboxymethyl chitosan were dissolved in 90 parts of 2% glacial acetic acid, stirred for 0.5h at a stirring rate of 300r / min, and after mixing evenly, 2 parts of montmorillonite and 3 parts of potassium humate were added, and 0.8 parts of sodium carbonate and 0.3 parts of sodium dodecylbenzene sulfonate were added at the same time. After stirring at a temperature of 50°C for 2h, 1 part of eicosanedial was added to form a preliminary adsorption gel containing a Schiff base structure through cross-linking;

[0030] Step three, dissolve 2-methylimidazole and cobalt nitrate hexahydrate in a mixed solution of methanol and water, and stir until the solution is clear and uniform, wherein the mass ratios of 2-methylimidazole, nitric acid hexahydrate, methanol and water are 0.7:0.5:30:25 respectively; at the same time, add the preliminary adsorption gel prepared in step two, the mass ratio of the mixed solution to the preliminary adsorption gel prepared in step two is 7:9, stir at a stirring rate of 500r / min for 2h, and freeze-dry for 24h to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure.

[0031] Example 2

[0032] This embodiment provides a method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, comprising the following steps:

[0033] Step 1: According to the mass fraction, 20 parts of zinc acetate and 15 parts of tin tetrachloride were weighed, dissolved in 85 parts of water, and hydrothermally reacted at 90°C for 10 hours. The solid product was separated, washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to obtain ZnSn(OH) 6 , further dispersed it in 25 parts of hydrochloric acid solution with a pH of 4 to obtain suspension A; weighed 0.8 parts of GO and dispersed it in 20 parts of water to obtain suspension B; slowly added suspension B to suspension A, and after irradiating with ultraviolet light for 1 hour, ultrasonicated for 0.5 hours, stirred for 3 hours, and allowed to stand for 3 hours, the solid product was separated and washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to finally obtain rGO / ZnSn(OH) 6 Composite materials;

[0034] Step 2: According to the mass fraction, 4 parts of rGO / ZnSn(OH) 6 and 2 parts of chitosan oligosaccharide dissolved in 80 parts of 2% glacial acetic acid, fully stirred at a stirring rate of 400r / min, and after mixing evenly, 2 parts of montmorillonite and 2 parts of potassium humate were added, and 0.5 parts of sodium bicarbonate and 0.4 parts of sodium stearate were added at the same time, and 2 parts of glutaraldehyde were added after stirring at a temperature of 40°C for 1h to form a preliminary adsorption gel containing a Schiff base structure through cross-linking;

[0035] Step three, dissolve 2-methylimidazole and cobalt nitrate hexahydrate in a mixed solution of methanol and water, and stir until the solution is clear and uniform, wherein the mass ratios of 2-methylimidazole, nitric acid hexahydrate, methanol, and water are 0.6:0.4:40:25 respectively; at the same time, add the preliminary adsorption gel prepared in step two, the mass ratio of the mixed solution to the preliminary adsorption gel prepared in step two is 50:85, stir at a stirring rate of 500r / min for 2h, and freeze-dry for 24h to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure.

[0036] Example 3

[0037] This embodiment provides a method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, comprising the following steps:

[0038] Step 1: According to the mass fraction, 15 parts of zinc acetate and 10 parts of tin tetrachloride were weighed, dissolved in 90 parts of water, and hydrothermally reacted at 90°C for 10 hours. The solid product was separated, washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to obtain ZnSn(OH) 6, further dispersed it in 25 parts of hydrochloric acid solution with a pH of 4 to obtain suspension A; weighed 0.7 parts of GO and dispersed it in 20 parts of water to obtain suspension B; slowly added suspension B to suspension A, and after irradiating it with ultraviolet light for 1 hour, ultrasonicated it for 0.5 hours, stirred it for 3 hours, and allowed to stand for 3 hours. The solid product was separated and washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to finally obtain rGO / ZnSn(OH) 6 Composite materials;

[0039] Step 2: According to the mass fraction, 4 parts of rGO / ZnSn(OH) 6 and 3 parts of hyaluronic acid are dissolved in 95 parts of 2% glacial acetic acid, stirred thoroughly at a stirring rate of 500r / min, and after mixing evenly, 1 part of montmorillonite and 2 parts of potassium humate are added, and at the same time, 0.6 parts of polymethacrylate and 0.5 parts of sodium oleate are added, and after stirring at a temperature of 50°C for 2h, 1 part of acrolein is added to form a preliminary adsorption gel containing a Schiff base structure through cross-linking;

[0040] Step 3: dissolve 2-methylimidazole and cobalt nitrate hexahydrate in a mixed solution of methanol and water, and stir until the solution is clear and uniform, wherein the mass ratios of 2-methylimidazole, nitric acid hexahydrate, methanol and water are 0.8:0.4:35:25 respectively; at the same time, add the preliminary adsorption gel prepared in step 2, the mass ratio of the mixed solution to the preliminary adsorption gel prepared in step 2 is 75:110, stir at a stirring rate of 400r / min for 2h, and freeze-dry for 24h to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure.

[0041] Example 4

[0042] This embodiment provides a method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, comprising the following steps:

[0043] Step 1: According to the mass fraction, 15 parts of zinc acetate and 15 parts of tin tetrachloride were weighed, dissolved in 80 parts of water, and hydrothermally reacted at 90°C for 9 hours. The solid product was separated, washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to obtain ZnSn(OH) 6 , further dispersed it in 20 parts of hydrochloric acid solution with a pH of 4 to obtain suspension A; weighed 0.7 parts of GO and dispersed it in 30 parts of water to obtain suspension B; slowly added suspension B to suspension A, and after irradiating with ultraviolet light for 0.8 hours, ultrasonicated for 0.6 hours, stirred for 2.5 hours, and allowed to stand for 4 hours, the solid product was separated and washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to finally obtain rGO / ZnSn(OH) 6 Composite materials;

[0044] Step 2: According to the mass fraction, 5 parts of rGO / ZnSn(OH) 6 and 2 parts of gelatin dissolved in 100 parts of 2% glacial acetic acid, fully stirred at a stirring rate of 300r / min, and after mixing evenly, 2 parts of montmorillonite and 2 parts of potassium humate were added, and 0.7 parts of polyvinyl alcohol and 0.5 parts of sodium oleate were added at the same time, and 1.5 parts of succinaldehyde were added after stirring at a temperature of 45°C for 2h to form a preliminary adsorption gel containing a Schiff base structure through cross-linking;

[0045] Step 3: dissolve 2-methylimidazole and cobalt nitrate hexahydrate in a mixed solution of methanol and water, and stir until the solution is clear and uniform, wherein the mass ratios of 2-methylimidazole, nitric acid hexahydrate, methanol and water are 0.7:0.5:35:30 respectively; at the same time, add the preliminary adsorption gel prepared in step 2, the mass ratio of the mixed solution to the preliminary adsorption gel prepared in step 2 is 60:100, stir at a stirring rate of 400r / min for 1h, and freeze-dry for 24h to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure.

[0046] Example 5

[0047] This embodiment provides a method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, comprising the following steps:

[0048] Step 1: According to the mass fraction, 18 parts of zinc acetate and 15 parts of tin tetrachloride were weighed, dissolved in 100 parts of water, and hydrothermally reacted at 95°C for 8 hours. The solid product was separated, washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to obtain ZnSn(OH) 6 , further dispersed it in 30 parts of hydrochloric acid solution with a pH of 4 to obtain suspension A; weighed 0.5 parts of GO and dispersed it in 26 parts of water to obtain suspension B; slowly added suspension B to suspension A, and after irradiating with ultraviolet light for 0.5 hours, ultrasonicated for 1 hour, stirred for 2 hours, and allowed to stand for 5 hours, the solid product was separated and washed with distilled water for 3 times, and dried in an oven at 80°C for 10 hours to finally obtain rGO / ZnSn(OH) 6 Composite materials;

[0049] Step 2: Mix 3 parts of rGO / ZnSn(OH) 6 and 1 part of carboxymethyl chitosan were dissolved in 92 parts of 2% glacial acetic acid, stirred thoroughly at a stirring rate of 500 r / min, and after mixing evenly, 1.5 parts of montmorillonite and 1 part of potassium humate were added, and 0.7 parts of sodium bicarbonate and 0.4 parts of sodium stearate were added at the same time. After stirring at a temperature of 50°C for 1.5 hours, 1 part of acrolein was added to form a preliminary adsorption gel containing a Schiff base structure through cross-linking;

[0050] Step three, dissolve 2-methylimidazole and cobalt nitrate hexahydrate in a mixed solution of methanol and water, and stir until the solution is clear and uniform, wherein the mass ratios of 2-methylimidazole, nitric acid hexahydrate, methanol and water are 0.8:0.6:35:20 respectively; at the same time, add the preliminary adsorption gel prepared in step two, the mass ratio of the mixed solution to the preliminary adsorption gel prepared in step two is 60:110, stir at a stirring rate of 300r / min for 1.5h, and freeze-dry for 24h to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure.

[0051] In order to characterize the adsorption performance of the high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure, the adsorption effect and photocatalytic adsorption degradation of the high-performance photocatalytic synergistic adsorption material of ZIF-67 nanostructure synthesized in the embodiment were tested. The adsorbed methylene blue, rhodamine B, Pb 2+ The solution with an initial concentration of 200 mg / L, and the solution with an initial concentration of 100 mg / L for phenol and benzene were placed in a constant temperature oscillating box at 298K, 308K and 318K for 300-350 min, centrifuged and left to stand for 30 min, and then the absorbance of the supernatant was measured at 662 nm and 540 nm using a visible spectrophotometer. The removal rate after adsorption was calculated using formula (1):

[0052]

[0053] In formula (1), C 0 and C e They represent initial concentration and equilibrium concentration respectively, in mg / L; R is the removal rate at equilibrium.

[0054] Calculate the removal rate of each substance, as shown in Table 1:

[0055] Table 1 Removal rate of various pollutants by ZIF-67 nanostructured high-performance photocatalytic synergistic adsorption materials

[0056]

[0057] Under (500W) ultraviolet light irradiation, the photocatalytic removal rate of each substance was calculated, and the results are shown in Table 2:

[0058] Table 2 Photocatalytic removal rate of various pollutants by ZIF-67 nanostructured high-performance photocatalytic synergistic adsorption materials

[0059]

[0060] Through the analysis of the above data, it is concluded that the high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure prepared by the present invention has an excellent effect on the common sewage pollutants such as methylene blue, rhodamine B, and Pb2+ Both have good adsorption removal rates. The adsorption amount of soil pollutants phenol and benzene is small. However, under the irradiation of ultraviolet light, due to the hydroxystannate composite reduced graphene structure contained in the adsorption material prepared by the present invention, not only the adsorption performance is improved, but also the treatment capacity of soil pollutants phenol and benzene is greatly improved under the joint action of photocatalysis and adsorption, and the pollution problems of dyes and heavy metal ions in water bodies and benzene and its homologues in the soil of coal mining areas are solved, realizing the concept of green and environmentally friendly treatment of pollutants.

[0061] The above content is a further detailed description of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, they can also make several simple deductions or substitutions, which should be regarded as belonging to the protection scope of the present invention determined by the submitted claims.

Claims

1. A method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure, characterized in that: The following steps are involved: Step 1: Weigh 10-20 parts of zinc acetate and 10-20 parts of tin tetrachloride by mass, dissolve them in 80-100 parts of water, and perform hydrothermal reaction at 85-95° C. for 8-10 hours. Separate the solid product, wash and dry it to obtain ZnSn(OH)6. Further disperse ZnSn(OH)6 in 20-30 parts of hydrochloric acid solution with a pH of 4 to obtain a suspension A. According to the mass fraction, 0.5-0.8 parts of GO were weighed and dispersed in 20-30 parts of water to obtain suspension B; The suspension B was slowly added dropwise to the suspension A, and after being irradiated with ultraviolet light for 0.5 to 1 hour, ultrasonicated for 0.5 to 1 hour, stirred for 2 to 3 hours, and allowed to stand for 3 to 5 hours, the solid product was separated, washed, and dried to finally obtain the rGO / ZnSn(OH)6 composite material; Step 2: Dissolve 3-5 parts of rGO / ZnSn(OH)6 and 1-3 parts of natural polysaccharide in 80-100 parts of 2% glacial acetic acid by weight, stir until well mixed, add 1-2 parts of montmorillonite and 1-3 parts of potassium humate, add 0.5-0.8 parts of porogen and 0.3-0.5 parts of surfactant, stir at 40-50°C for 1-2h, then add 1-2 parts of cross-linking agent to form a preliminary adsorption gel containing Schiff base structure by cross-linking; Step three, mix 2-methylimidazole, cobalt nitrate hexahydrate, methanol and water in a mass ratio of (0.6-0.8): (0.4-0.6): (30-40): (20-30), stir until the solution is clear and uniform to obtain a mixed solution, add the preliminary adsorption gel prepared in step 2 to the mixed solution in a mass ratio of (50-75): (85-110), stir for 1-2 hours, and freeze-dry to obtain a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructures.

2. The method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure according to claim 1, characterized in that: The natural polysaccharide includes any one of carboxymethyl chitosan, chitosan oligosaccharide, hyaluronic acid and gelatin.

3. The method for preparing a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructures according to claim 1, characterized in that: The porogen includes any one of sodium carbonate, sodium bicarbonate, polymethacrylate and polyvinyl alcohol.

4. The method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure according to claim 1, characterized in that: The surfactant includes any one of sodium dodecylbenzene sulfonate, sodium stearate and sodium oleate.

5. The method for preparing a high-performance photocatalytic synergistic adsorption material containing a ZIF-67 nanostructure according to claim 1, characterized in that: The cross-linking agent includes any one of glutaraldehyde, eicosanedial, acrolein, and succinaldehyde.

6. The method for preparing a high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructures according to claim 1, characterized in that: The stirring rate in step 2 and step 3 is 300-500 r / min.

7. A high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructures prepared by the method according to any one of claims 1 to 6.

8. Use of the high-performance photocatalytic synergistic adsorption material containing ZIF-67 nanostructure as claimed in claim 7 in water treatment or soil remediation.

Citation Information

Patent Citations

  • Photocatalyst-loaded Co-based MOFs-porous carbon composite adsorption material and preparation method thereof

    CN111111617A

  • High-load SA / GO / ZIFs composite adsorbent as well as preparation method and application thereof

    CN112619616A

  • Coal waste adsorption gel ball containing ZIF structure and preparation method and application thereof

    CN115518624A

  • Synthesis and application of mofs / natural polymers composite beads adsorbents

    WO2017133324A1

  • Preparation method for core-shell nanoparticles based on lipid membrane and metal organic framework

    WO2021103232A1

Cited By

  • Industrial wastewater purifying agent and preparation method thereof

    CN120861011A